2013
DOI: 10.1155/2013/869356
|View full text |Cite
|
Sign up to set email alerts
|

Using Software Dependency to Bug Prediction

Abstract: Software maintenance, especially bug prediction, plays an important role in evaluating software quality and balancing development costs. This study attempts to use several quantitative network metrics to explore their relationships with bug prediction in terms of software dependency. Our work consists of four main steps. First, we constructed software dependency networks regarding five dependency scenes at the class-level granularity. Second, we used a set of nine representative and commonly used metrics—namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Note that, except for mE-Weight, BC measure performs better than the proposed measures. The results further validated the advantage of BC measure as mentioned in [6,30]. Meanwhile, it is clear that mE-Weight measure performs best, which indicated that computing the centrality on the weighted edge of nodes has an advantage compared to that based on the node degree and even prior to other frequently used centrality measures.…”
Section: 4supporting
confidence: 60%
“…Note that, except for mE-Weight, BC measure performs better than the proposed measures. The results further validated the advantage of BC measure as mentioned in [6,30]. Meanwhile, it is clear that mE-Weight measure performs best, which indicated that computing the centrality on the weighted edge of nodes has an advantage compared to that based on the node degree and even prior to other frequently used centrality measures.…”
Section: 4supporting
confidence: 60%
“…In defect prediction literature, a considerable number of software metrics, such as static code metrics, code change history, process metrics and network metrics [10], have been used to construct different predictors for defect prediction [35]. Almost all existing prediction models are built on the complex combinations of software metrics, with which a prediction model usually can achieve a satisfactory accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies still ignore the structural features of programs, such as the dependencies between program files. Prior studies [12,[33][34][35] have demonstrated the effectiveness of network structure information in improving the performance of the defect prediction model. Nowadays, the node of a network can be represented as a low-dimensional vector by means of network embedding.…”
Section: 2mentioning
confidence: 99%
“…It can find the possible defective code blocks according to the features of historical data, thus allowing workers to focus their limited resources on the defect-prone code. Figure 2 presents a basic framework of software defect prediction and has been widely used in existing studies [1,8,12,18,19,24,25].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation